Mastoid Dimensions in Children and Young Adults: Consequences for the Geometry of Transcutaneous Bone-Conduction Implants. Issue 1 (January 2016) - Rahne, Torsten; Schilde, Sebastian; Seiwerth, Ingmar; Radetzki, Florian; Stoevesandt, Dietrich; Plontke, Stefan K.
Abstract : Objectives: Bone-conduction implants (BCI) are available for adults and children who are aged 5 years or more. Because a transcutaneous bone-conduction implant introduced in 2013 does not completely fit into all adult mastoids, we investigated mastoid dimensions and the possibility of fitting the implant in children. Design: Computed tomography scans of 151 mastoids from 80 children and young adolescents from the age of 5 months to 20 years and 52 control mastoids from 33 adults were retrospectively analyzed. After three-dimensional reconstruction, mastoid volume was measured. The chances of fitting the Bonebridge or a novel BCI were determined as a function of age. Implant diameter and implantation depths were virtually varied to identify the most advantageous dimensions for reducing the minimum age for implantation. Results: Mastoid volume increased to 13.8 ml in female and 16.4 ml in male adult mastoids at ages 18.9 years (male) and 19.0 years (female). Without compromising the middle fossa dura or the sinus and without lifts, the Bonebridge implant fit in 81% of male adult mastoids and 77% of the female adult mastoids. For children, the 50% chance of fitting a Bonebridge in the mastoids was reached at age 12 years; with a protrusion of 4 mm (4-mm lifts), this age was reduced to >6 years. The novel BCI fit in 100% of male and 94% of female adult mastoids. Conclusions: Casing diameter is the most limiting factor for Bonebridge implantation in children. A modified implant casing with a truncated cone and reduced diameter and volume would increase the number of hearing impaired children who can be rehabilitated with a Bonebridge implant. Radiological planning for Bonebridge implantation is necessary in all children.